2007
DOI: 10.1007/bf03194675
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cytogenetic characterization of eight small supernumerary marker chromosomes originating from chromosomes 2, 4, 8,18, and 21 in three patients

Abstract: Small supernumerary marker chromosomes (sSMCs) are a morphologically heterogeneous group of additional structurally abnormal chromosomes that cannot be identified unambiguously by conventional banding techniques alone. Molecular cytogenetic methods enable detailed characterization of sSMCs; however, in many cases interpretation of their clinical significance is problematic. The aim of our study was to characterize precisely sSMCs identified in three patients with dysmorphic features, psychomotor retardation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 47 publications
2
17
0
3
Order By: Relevance
“…Small supernumerary chromosomes (sSMC) of an unknown origin are commonly referred to as 'marker chromosomes' or 'ESACs' (extra structurally abnormal chromosomes) (Blennow et al 1993;Pietrzak et al 2007). They are found in an about 0.043% of the human population and have been estimated to result in an abnormal phenotype approximately 30% of sSMC carriers (Pietrzak et al 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Small supernumerary chromosomes (sSMC) of an unknown origin are commonly referred to as 'marker chromosomes' or 'ESACs' (extra structurally abnormal chromosomes) (Blennow et al 1993;Pietrzak et al 2007). They are found in an about 0.043% of the human population and have been estimated to result in an abnormal phenotype approximately 30% of sSMC carriers (Pietrzak et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…They are found in an about 0.043% of the human population and have been estimated to result in an abnormal phenotype approximately 30% of sSMC carriers (Pietrzak et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Cases of Tetrasomy 18p may have variable phenotypic characteristics. The cause of different phenotypic features may be chromosomal origin, euchromatin content, mosaicism, parental origin and genomic imprinting 8 . Callen et al 9 suggested that parental age might be advanced in the isochromosome 18p syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the standard aCGH, which uses dye reverse experiments as controls, there is no need for this when using microdissected DNA of interest because of the clear profiles at the expected regions. The rational of this approach was previously described for mapping of marker chromosome-derived DNA (Pietrzak et al 2007). …”
Section: Bac-based Acghmentioning
confidence: 99%